Hanne Darboven : Evolution Leibniz 1986. - Sprengel Museum, Hannover (Hannover : Sprengel Museum Hannover, 1996)
The 350th anniversary of the birth of Gottfried Wilhelm Leibniz has served as an external impetus for this premiere. The philosopher, mathematician, lawyer and political essayist was born in Leipzig in 1646 and died in Hannover in 1716.
biog.
Duits
Engels
Hanne Darboven : Evolution Leibniz 1986. Sprengel Museum Hannover. 1996-06-11. 1996-10-20
boek
Keywords: Darboven, Hanne